Житлові споруди середньовічного чернецтва на землях Українського Прикарпаття - Берест, Р. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Issues of peculiarities and evolution of manner of life and residences of medieval monks are analyzed at the article on the base of investigation of written sources and results of archaeological researches of complex of medieval monuments of Ukrainian Sub-Carpathian region.